2013
DOI: 10.7465/jkdi.2013.24.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture prediction using a support vector regression

Abstract: Soil moisture is a very important variable in various area of hydrological processes. We predict the soil moisture using a support vector regression. The model is trained and tested using the soil moisture data observed in five sites in the Yongdam dam basin. With respect to soil moisture data of of four sites-Jucheon, Bugui, Sangieon and Ahncheon which are used to train the model, the correlation coefficient between the esimtates and the observed values is about 0.976. As the result of the application to Cheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Additionally, [48], have used this technique for retrieving soil moisture from remote sensing data by combining backscatter from the Tropical Rainfall Measuring Mission (TRMM), and a normalized difference vegetation index (NDVI) from an advanced very high resolution radiometer (AVHRR), and they revealed that this technique performs better for soil moisture retrieval than the multivariate linear regression model (MLR). Recently, [59], confirmed the accuracy of the SVR model to predict soil moisture from soil temperature, NDVI, rainfall, and soil moisture observed the day before. To our knowledge, although SVR has been used in past studies for soil moisture retrieval, none of the studies have tested this algorithm with high resolution radar data.…”
Section: Introductionmentioning
confidence: 71%
“…Additionally, [48], have used this technique for retrieving soil moisture from remote sensing data by combining backscatter from the Tropical Rainfall Measuring Mission (TRMM), and a normalized difference vegetation index (NDVI) from an advanced very high resolution radiometer (AVHRR), and they revealed that this technique performs better for soil moisture retrieval than the multivariate linear regression model (MLR). Recently, [59], confirmed the accuracy of the SVR model to predict soil moisture from soil temperature, NDVI, rainfall, and soil moisture observed the day before. To our knowledge, although SVR has been used in past studies for soil moisture retrieval, none of the studies have tested this algorithm with high resolution radar data.…”
Section: Introductionmentioning
confidence: 71%
“…In recent years, the SVR-based models have been able to offer accurate assessments regarding the geotechnical problems (e.g., [34][35][36][37]). The phenomena related to soil environments as well as the earthquake-induced loadings are highly complex [38][39][40].…”
Section: -Introductionmentioning
confidence: 99%